Drug-Induced Anaphylaxis: National Database Analysis - Olga Butranova; Sergey Zyryanov; Anastasia Gorbacheva; Irina Asetskaya; Vitaly Polivanov (MDPI AG, 2024)
(1) Background: National health system databases represent an important source of information about the epidemiology of adverse drug reactions including drug-induced allergy and anaphylaxis. Analysis of such databases may enhance the knowledge of healthcare professionals regarding the problem of drug-induced anaphylaxis. (2) Methods: A retrospective descriptive analysis was carried out of spontaneous reports (SRs) with data on drug-induced anaphylaxis (SRsAs) extracted from the Russian National Pharmacovigilance database (analyzed period 2 April 2019-21 June 2023). The percentage of SRsAs among SRs of drug-induced allergy (SRsDIAs) was calculated, as well as of pediatric, elderly, and fatal SrsAs. Drugs involved in anaphylaxis were assessed among total SRsAs, pediatric, and elderly SRsAs, and among fatal SRsAs. Demographic parameters of patients were assessed. (3) Results: SRsAs were reported in 8.3% of SRsDIAs (2304/27,727), the mean age of patients was 48.2 ± 15.8 years, and females accounted for 53.2% of cases. The main causative groups of drugs were antibacterials (ABs) for systemic use (44.6%), local anesthetics (20.0%), and cyclooxygenase (COX) inhibitors (10.1%). Fatal SRsAs were reported in 9.5% (218/2304) of cases, the mean age of patients was 48.0 ± 16.7 years, and females accounted for 56.4% of cases. Pediatric SRsAs accounted for 3.9% of pediatric SRsDIAs and 5.8% of all SRsAs, with a mean age of 11.8 ± 4.5 years, and females acccounted for 51.9% of cases. Elderly SRsAs accounted for 2% of elderly SRsDIAs and 2.8% of all SRsAs, and the mean age was 73.0 ± 5.3 years, and females accounted for 43.5% of cases. ABs caused 40% of SRsAs in the elderly, 42.9% in children, and 50% of fatal SRsAs. (4) Conclusions: Our study revealed a relatively high proportion of anaphylaxis among SRs of drug-induced allergy. ABs were the most prevalent causative agents, especially in fatal SRsAs.